PENINGKATAN KEMAMPUAN GURU MELALUI SUPERVISI PENDIDIKAN - Irma Setya Ningsih; Chelina Aurilia Purwanto; Munawir Munawir (PEDIR: Journal of Elementary Education, 2021)
The teacher has an important role in a learning process. The success of a learning is largely determined by the ability of teachers to manage learning activities in the classroom. Thus, teachers are expected to continue to develop their abilities in planning, implementing, and improving learning in a systematic and directed manner in order to improve the process and learning outcomes of participants. Supervision is a planned effort in improving the quality of education in an institution. In this case, educational supervision needs to be carried out to provide services and facilities to teachers to develop teacher abilities, especially in pedagogic competence and professionalism. In its implementation, the head of the madrasa acts as a supervisor to observe the learning activities carried out by the teacher. Educational supervision activities can be carried out individually or in groups by taking into account the principles of scientific, democratic, cooperative, as well as constructive and creative.